Tumour microenvironment in pheochromocytoma and paraganglioma - Martinelli, Serena; Amore, Francesca; Canu, Letizia; Maggi, Mario; Rapizzi, Elena (Frontiers in Endocrinology, 2023)
Pheochromocytomas and Paragangliomas (Pheo/PGL) are rare catecholamine-producing tumours derived from adrenal medulla or from the extra-adrenal paraganglia respectively. Around 10–15% of Pheo/PGL develop metastatic forms and have a poor prognosis with a 37% of mortality rate at 5 years. These tumours have a strongly genetic determinism and succinate dehydrogenase B (SDHB) mutations are highly associated with metastatic forms. To date, no effective treatment is present for metastatic forms. In addition to cancer cells, the tumour microenvironment (TME) is also composed of non-neoplastic cells and non-cellular components, which are essential for tumour initiation and progression in multiple cancers, including Pheo/PGL. This review, for the first time, provides an overview of the roles of TME cells such as cancer-associated fibroblasts (CAFs) and tumour-associated macrophages (TAMs) on Pheo/PGL growth and progression. Moreover, the functions of the non-cellular components of the TME, among which the most representatives are growth factors, extracellular vesicles and extracellular matrix (ECM) are explored. The importance of succinate as an oncometabolite is emerging and since Pheo/PGL SDH mutated accumulate high levels of succinate, the role of succinate and of its receptor (SUCNR1) in the modulation of the carcinogenesis process is also analysed. Further understanding of the mechanism behind the complicated effects of TME on Pheo/PGL growth and spread could suggest novel therapeutic targets for further clinical treatments.